Necrostatin-1 Ameliorates Peripheral Nerve Injury-Induced Neuropathic Pain by Inhibiting the RIP1/RIP3 Pathway - Liang, Ying-Xia; Wang, Nan-Nan; Zhang, Zhi-Yu; Juan, Zhao-Dong; Zhang, Can (Frontiers in Cellular Neuroscience, 2019)
Necrostatin-1 is an inhibitor of necroptosis, a form of programmed cell death that has been reported to be involved in various neurological diseases. Presently, the role of necroptosis in neuropathic pain induced by peripheral nerve injury is still unclear. This study was focused on investigating the potential effects of necroptosis in the development and progression of neuropathic pain in a rat model and the possible neuroprotective effects of necrostatin-1 in neuropathic pain. The results indicated that the necroptosis-related proteins RIP1 and RIP3 significantly increased postoperation in the spinal cord in a neuropathic pain model and peaked 7 days postoperation, which was consistent with the time-dependent changes of hyperalgesia. Additionally, we found that peripheral nerve injury-related behavioral and biochemical changes were significantly reduced by necrostatin-1. In particular, hyperalgesia was attenuated, and the levels of RIP1 and RIP3 were decreased. Furthermore, the ultrastructure of necrotic cell death and neuroinflammation were alleviated by necrostatin-1. Collectively, these results suggest that necroptosis is an important mechanism of cell death in neuropathic pain induced by peripheral nerve injury and that necrostatin-1 may be a promising neuroprotective treatment for neuropathic pain.